2012
DOI: 10.1155/2012/352510
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration in Artificial Jaw Cleft by Use of Carbonated Hydroxyapatite Particles and Mesenchymal Stem Cells Derived from Iliac Bone

Abstract: Objectives of the Study. Cleft lip and palate (CLP) is a prevalent congenital anomaly in the orofacial region. Autogenous iliac bone grafting has been frequently employed for the closure of bone defects at the jaw cleft site. Since the related surgical procedures are quite invasive for patients, it is of great importance to develop a new less invasive technique. The aim of this study was to examine bone regeneration with mesenchyme stem cells (MSCs) for the treatment of bone defect in artificially created jaw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 17 publications
(13 reference statements)
3
40
0
3
Order By: Relevance
“…Yoshioka and et al 17 superior to β-TCP alone, and that MSC allowed for proper physiological function and successful tooth movement with adequate bone support.…”
Section: Preclinical Studies On Animal Modelsmentioning
confidence: 98%
See 2 more Smart Citations
“…Yoshioka and et al 17 superior to β-TCP alone, and that MSC allowed for proper physiological function and successful tooth movement with adequate bone support.…”
Section: Preclinical Studies On Animal Modelsmentioning
confidence: 98%
“…MSC in combination with biomaterials, carry a great potential that has already been proven in animal studies and on first human cases. [17][18][19][20][21][22][23][24][25][26][27][28] Several aspects have to be taken into consideration when planning stem cell-enhanced bone regeneration.…”
Section: Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 studies reported success of alveolar defect repair using DPSC [132], BMSC/PRF [130], Adipose derived stem cells [131] and mesenchymal stem cells derived from iliac bone [133].…”
Section: Cleft Palatementioning
confidence: 99%
“…The X-ray and histological examination revealed that the regenerated bone on the experimental side was almost equivalent to the original bone adjoining the jaw cleft. It was suggested the application of MSCs with Carbonated Hydroxyapatite (CAP) particles can become a new treatment modality for bone regeneration for cleft lip and palate patients [133].…”
Section: Cleft Palatementioning
confidence: 99%